Penyelesaian Konflik Lingkungan dalam Pengelolaan Sampah di Kabupaten Bantul - Nafis, Wildan (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
This research used qualitative method. The data were collected with participant observation and study of literature that processed by descriptive and schematic. The research is located at TPST Piyungan Bantul Daerah Istimewa Yogyakarta. The location selection is based on intensity of waste management environmental conflicts. The factors that cause conflict in the waste management environment in Bantul Regency are: the resolution has not been maximal, the absence of integrated and and fast conflict prevention measures, there is an attitude of neglect by public policy makers, there is no good communication between waste collection workers and community members with the TPST managers or administrators as well as with the local government, including the lack of communication and the absence of significant follow-up responses to complaints from lower levels to stakeholders. The authority of Piyungan TPSTwhich is directly under the DIY Regional Government is considered not optimal in responding to the needs for management facilities and infrastructure at Piyungan TPST. It can be seen that the anticipatory steps taken are still sporadic, even though there are policies that are bisaed against them, but they are often difficult to implement because of the lack of supervision and innovation. The conflict of authority between the policy-making agencies is a pattern of resolution after the problem arises. It needs detail policy instrument to reorganize waste management so that conflicts do not last long and increase, so that conflicts do not occur openly and again. Waste sorting is intensified at all layers before being transported to Piyungan TPST, so that when it arrives at Piyungan, the waste is already in its final stage. Encourage and facilitate waste management in all villages in Bantul. Modernization of waste processing equipment into fertilizer and energy can be used to supply electricity needs. In order to prevent environmental damage from occurring, development as an effort to increase human dignity should have a strategy that truly considers multi-factor and sustainable.